Changing trend in disease burden of mental illness and its risk factors in China, 1990 - 2019 - Juan-juan LI; Shu-yong ZHAO; Yuan-ze DU (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo explore changing trend in disease burden of mental illness and its risk factors in Chinese popula-tion from 1990 to 2019 for providing evidences to prevention and treatment of mental illness. MethodsThe open data of the Global Burden of Disease Study (GBD) were used in the study. Age-sex-specific prevalence rate, years lived with disability (YLDs) and disability-adjusted life years (DALYs) for 1990, 2000, 2010 and 2019 were adopted to describe the burden of mental illness and combined with population attributable fraction (PAF) to assess the changing trend in the burden. ResultsAmong Chinese residents in 2019, the rate (1/100 000) for mental illness prevalence, YLDs and DALYs were 12 055.47, 1 426.78 and 1 426.62; the rates increased with the increment of age among the residents of various age groups, with the highest rates in the residents aged 50 - 69 years; compared to those in female residents, the rates were lower in male residents (prevalence: 10 886.21 vs. 11 649.28, YLDs: 1 294.39 vs. 1564.03, DALYs: 1 294.51 vs. 1 564.22). The DALYs (million person years) attributed to child sexual abuse and intimate partner violence increased from 1.063 and 3.094 in 1990 to 1.404 and 3.801 in 2019, with the increases of 32.04% and 22.87%. The DALYs attributed to bullying victimization, child sexual abuse and bullying, lead exposure and other environmental risks declined, with the highest decrease of 39.58% for both DALYs attributed to lead exposure and other environmental hazards. In comparison to that in 1990, the PAF of DALYs attributed to child sexual abuse increased by 1.73% in 2019; however, the PAF of DALYs attributed to bullying, child sexual abuse and bullying, intimate partner violence, lead exposure, and other environmental hazards decreased by 49.17%, 40.09%, 5.39%, 53.47%, and 53.47%, respectively. The DALYs due to intimate partner violence rose but that due to bullying declined during 2010 - 2019. Conclusion The disease burden of mental illness gradually increased from 1990 to 2019 among residents in China and disability was a main contributor to the burden. Psychological education and counseling should be promoted among the residents, especially among the elderly women at a higher risk of mental illness.